The role of procalcitonin and C-reactive protein in predicting candidemia in reanimation intensive care unit and burn unit patients (Annals of Medical Research, 2021)
Aim: Predicting the diagnosis of candidemia remains a challenge for physicians. It is difficult to distinguish candidemia from other potential conditions, especially in patients under intensive care. Although blood culture is the gold standard in diagnosis, there is continued search for other markers that may be used for early prediction.This study intended to assess if procalcitonin (PCT) and C-reactive protein (CRP) may be able to guide the course of Candidemia.Materials and Methods: The study included patients over the age of 18 admitted to the Reanimation Intensive Care Unit and Burn Unit between June 2018 and June 2019 whose blood cultures exhibited growth of Candida species (spp.). Moreover, the patients’ blood cultures were also tested for Gram negative and Grow positive bacterial growth that may accompany Candida species (spp.). For all patients, we recorded the PCT and CRP values three times.Results: This study examined sixty-six patients exhibiting growth of Candida spp. in their blood cultures; 42 (64%) cases had no accompanying bacterial growth in their culture (Group 1). In addition to the growth of Candida spp., the blood cultures showed that 16 patients also had Gram-negative bacteremia (Group 2), and eight patients had Gram-positive bacteremia (Group 3). When a cut-off value of 0.5 ng/mL was considered for all candidemia patients, the first assessments did not show a statistically significant high value (p=0.053). However, when evaluated with bacteremia, the first PCT results were higher in patients with Gram-negative bacteremia. PCT and CRP changes over time were statistically significant based on two-way repeated measures comparisons (p0.05). There was a positive correlation between PCT values and mortality (p0.01).Conclusion: We believe that the decrease in PCT and CRP values are helpful while clinically monitoring patients with candidemia.